Stability in the South, Turbulence Toward the North: Evolutionary History of Aurinia saxatilis (Brassicaceae) Revealed by Phylogenomic and Climatic Modelling Data - Rešetnik, Ivana; Záveská, Eliška; Grgurev, Marin; Bogdanović, Sandro; Bartolić, Paolo; Frajman, Božo (Frontiers in Plant Science, 2022)
The Balkan Peninsula played an important role in the evolution of many Mediterranean plants and served as a major source for post-Pleistocene colonisation of central and northern Europe. Its complex geo-climatic history and environmental heterogeneity significantly influenced spatiotemporal diversification and resulted in intricate phylogeographic patterns. To explore the evolutionary dynamics and phylogeographic patterns within the widespread eastern Mediterranean and central European species Aurinia saxatilis, we used a combination of phylogenomic (restriction-site associated DNA sequencing, RADseq) and phylogenetic (sequences of the plastid marker ndhF) data as well as species distribution models generated for the present and the Last Glacial Maximum (LGM). The inferred phylogenies retrieved three main geographically distinct lineages. The southern lineage is restricted to the eastern Mediterranean, where it is distributed throughout the Aegean area, the southern Balkan Peninsula, and the southern Apennine Peninsula, and corresponds to the species main distribution area during the LGM. The eastern lineage extends from the eastern Balkan Peninsula over the Carpathians to central Europe, while the central lineage occupies the central Balkan Peninsula. Molecular dating places the divergence among all the three lineages to the early to middle Pleistocene, indicating their long-term independent evolutionary trajectories. Our data revealed an early divergence and stable in situ persistence of the southernmost, eastern Mediterranean lineage, whereas the mainland, south-east European lineages experienced more complex and turbulent evolutionary dynamics triggered by Pleistocene climatic oscillations. Our data also support the existence of multiple glacial refugia in southeast Europe and highlight the central Balkan Peninsula not only as a cradle of lineage diversifications but also as a source of lineage dispersal. Finally, the extant genetic variation within A. saxatilis is congruent with the taxonomic separation of peripatric A. saxatilis subsp. saxatilis and A. saxatilis subsp. orientalis, whereas the taxonomic status of A. saxatilis subsp. megalocarpa remains doubtful.